Differentiation of bacterial and viral pneumonia in children - Virkki, R (BMJ Group, 2002)
Background: A study was undertaken to investigate the differential diagnostic role of chest radiographic findings, total white blood cell count (WBC), erythrocyte sedimentation rate (ESR), and serum C reactive protein (CRP) in children with community acquired pneumonia of varying aetiology. Methods: The study population consisted of 254 consecutive children admitted to hospital with community acquired pneumonia diagnosed between 1993 and 1995. WBC, ESR, and CRP levels were determined on admission. Seventeen infective agents (10 viruses and seven bacteria) were searched for. Chest radiographs were retrospectively and separately reviewed by three paediatric radiologists. Results: A potential causative agent was found in 215 (85%) of the 254 cases. Bacterial infection was found in 71% of 137 children with alveolar infiltrates on the chest radiograph, while 72% of the 134 cases with a bacterial pneumonia had alveolar infiltrates. Half of the 77 children with solely interstitial infiltrates on the chest radiograph had evidence of bacterial infection. The proportion of patients with increased WBC or ESR did not differ between bacterial and viral pneumonias, but differences in the CRP levels of >40 mg/l, >80 mg/l, and >120 mg/l were significant although the sensitivity for detecting bacterial pneumonia was too low for use in clinical practice. Conclusions: Most children with alveolar pneumonia, especially those with lobar infiltrates, have laboratory evidence of a bacterial infection. Interstitial infiltrates are seen in both viral and bacterial pneumonias.